2005
DOI: 10.3171/foc.2005.19.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis in the study of brain tumors: findings and applications

Abstract: Classic cytogenetics has evolved from black and white to technicolor images of chromosomes as a result of advances in fluorescence in situ hybridization (FISH) techniques, and is now called molecular cytogenetics. Improvements in the quality and diversity of probes suitable for FISH, coupled with advances in computerized image analysis, now permit the genome or tissue of interest to be analyzed in detail on a glass slide. It is evident that the growing list of options for cytogenetic analysis has impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 289 publications
(308 reference statements)
0
20
0
Order By: Relevance
“…LOH in the proximal region of human chromosome 18q has been reported in human squamous cell, ovarian, and prostate cancers (23)(24)(25). Moreover, LOH of human chromosome 18q has been reported in astrocytomas specimens (26,27). cDNA macroarray and microarray experiments have not yet reported a significant loss of GATA6 expression in human GBM due to a lack GATA6 on the arrays or to the method of analysis (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…LOH in the proximal region of human chromosome 18q has been reported in human squamous cell, ovarian, and prostate cancers (23)(24)(25). Moreover, LOH of human chromosome 18q has been reported in astrocytomas specimens (26,27). cDNA macroarray and microarray experiments have not yet reported a significant loss of GATA6 expression in human GBM due to a lack GATA6 on the arrays or to the method of analysis (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, data from the Cancer Genome Project obtained from the analyses of astrocytoma specimens using SNP arrays, methylation arrays, cDNA microarrays, comparative genomic hybridization arrays, spectral karyotyping, and standard cytogenetic analysis initially demonstrated that as many as 80% of specimens had chromosome 14 deletions (including NPAS3 cytogenetic interval) and aberrant NPAS3 expression. [2][3][4][5][6][7][8][9] Moreover, recently refined molecular classifications of glioblastomas using genomics-based methods have identified chromosome 14 deletions with NPAS3, which are common in the proneural subtype, followed by the mesenchymal and neural subtypes, but with none detected in the classic subtype. 2 To further strengthen the link between NPAS3 and neoplasia, chromosome 14 deletion leading to expected loss of NPAS3 expression has also been reported in oligodendrogliomas, mixed gliomas, and nonglial tumors including esophageal, breast, prostate gland, and renal carcinomas, and melanomas, 5,21-23 compared with normal control tissues.…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, recent molecular classification studies using genomicsbased approaches have further established glioblastomas as among the neural, proneural, mesenchymal, and classic subtypes. 2 The ongoing Cancer Genome Project [2][3][4][5][6][7][8][9] has identified more than 220 minimally critical regions in the human genome including a deletion of the locus containing the NPAS3 gene, which may be involved in the pathogenesis of high-grade astrocytomas.…”
mentioning
confidence: 99%
“…A range of characteristic genetic changes have been observed, which in high-grade gliomas are variable and complex (reviewed by Bayani et al, 2005 ). Benign tumor types are characterized by fewer changes, the most prominent being alteration of chromosome 22.…”
Section: Chromosomal Alterations In Brain Tumorsmentioning
confidence: 99%